Use of low-friction, fast-response and wave-absorbing integrated coating based on magnetic oil-containing microcapsules and method for preparing the same

CN118879109BActive Publication Date: 2026-10-27LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411133169.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2026-10-27
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

[0003]目前的自润滑涂层大多采用固体润滑填料,如石墨、二硫化钼、PTFE等,虽然涂层的稳态摩擦系数可以达到0.1~0.2,但是这一类固体润滑填料需要一定的跑合时间才可以在涂层表面(摩擦界面)处形成连续的摩擦润滑膜;在变工况条件下,这一类摩擦润滑膜局部可能会被破坏,膜层不连续,导致润滑效果衰减,直到新的摩擦润滑膜层形成,因此对变工况的响应速度较低

Benefits of technology

(1)本申请通过采用磁性含油微胶囊作为润滑填料,在摩擦过程中,润滑油从微胶囊内释放,在极短的时间内在涂层表面(摩擦界面)铺展形成润滑膜层;磁性纳米粒子能够修补磨痕缺陷,并增强润滑油与摩擦界面的相互作用;这二者的协同构效关系大大降低跑合时间,实现低摩擦超快响应。磁性纳米粒子的电磁损耗特性和微胶囊的空腔结构协同提升了材料的吸波性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118879109B_ABST
    Figure CN118879109B_ABST
Patent Text Reader

Abstract

The application provides a use of a low-friction quick-response and wave-absorbing integrated coating based on magnetic oil-containing microcapsules and a preparation method thereof. The coating is used for preparing a material integrating anticorrosion and wave-absorbing performance. The coating is prepared from a coating material composed of the following components in percentage by weight: 15-25% of epoxy resin, 5-15% of a curing agent, 1-5% of magnetic oil-containing microcapsules, and the balance of a solvent. The magnetic oil-containing microcapsules comprise a microcapsule shell material, ionic liquid and lubricating oil wrapped in the microcapsule shell material, and the microcapsule shell material comprises wall capsule monomers and magnetic nanoparticles embedded in the wall capsule monomers. The coating preparation method comprises the following steps: preparation of the magnetic oil-containing microcapsules, preparation of a magnetic oil-containing microcapsule slurry, preparation of the coating material, and preparation of the coating. The coating has low friction, quick response and good wave-absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of functional materials technology, and in particular to the application and preparation method of a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules. Background Technology

[0002] While the rapid development of electronic technology has brought convenience to mankind, it has also generated a large amount of electromagnetic pollution, interfering with the stable operation of precision equipment. As high-end equipment continues to develop towards larger scale, greater precision, and greater integration, the electromagnetic compatibility issues between precision devices cannot be ignored, necessitating high-performance absorbing coatings. In the military field, due to the rapid development of radar reconnaissance technology and precision-guided weapons, the survivability of equipment largely depends on its stealth performance, making stealth coatings an important direction for future defense development. From the perspective of service environment and operating conditions, a large number of moving parts on equipment, including various rotating mechanisms, power and transmission devices, also face conditions such as friction and wear, and corrosion-wear coupling, leading to problems such as surface damage and seizing of moving parts. Self-lubricating coatings can be applied to almost all friction components without changing the design and dimensions of the parts, making them one of the current research priorities. However, most research focuses primarily on the steady-state friction coefficient of self-lubricating coatings, paying less attention to the running-in phase. Yet, the friction and wear of most moving parts mainly occur during equipment start-up and shutdown, while friction and wear during steady-state operation are relatively minor. In conclusion, the development of high-performance, low-friction, fast-response, and integrated microwave absorbing coatings is of significant research and development importance and has promising application prospects in reducing friction and wear of moving parts, lowering maintenance costs, ensuring stable operation of equipment in complex electromagnetic environments, and improving equipment survivability.

[0003] Most current self-lubricating coatings use solid lubricating fillers, such as graphite, molybdenum disulfide, and PTFE. Although the steady-state friction coefficient of the coating can reach 0.1 to 0.2, these solid lubricating fillers require a certain running-in time to form a continuous friction lubrication film on the coating surface (friction interface). Under varying operating conditions, this type of friction lubrication film may be locally damaged, resulting in discontinuous film layers and reduced lubrication effect until a new friction lubrication film layer is formed. Therefore, the response speed to varying operating conditions is relatively low. Summary of the Invention

[0004] This application provides the use and preparation method of a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules, in order to solve the aforementioned problems mentioned in the background art.

[0005] On one hand, this application provides the use of a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules, which is used to prepare materials with integrated anti-corrosion and microwave-absorbing properties. The coating is composed of the following components by weight percentage: 15-25% epoxy resin, 5-15% curing agent, 1-5% magnetic oil-containing microcapsules, and the balance being solvent.

[0006] Magnetic oil-containing microcapsules include a microcapsule shell material and an ionic liquid and lubricating oil encapsulated within the microcapsule shell material. The microcapsule shell material includes a wall capsule monomer and magnetic nanoparticles embedded within the wall capsule monomer.

[0007] The solvent used is a mixture of xylene and n-butanol in a weight ratio of 1:1-2.

[0008] Optionally, the wall capsule monomer can be any one of silica sol, urea-formaldehyde resin, acrylic resin, or polyurethane resin.

[0009] Optionally, the curing agent is an amine-based curing agent.

[0010] On the other hand, this application provides a method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules, which is used to prepare the above-mentioned low-friction, fast-response, and microwave-absorbing integrated coating. The preparation method includes the following steps: (1) Preparation of magnetic oil-containing microcapsules: The composite emulsifier was dissolved in deionized water to form a clear solution, and the magnetic nanoparticles were ultrasonically dispersed in the clear solution to obtain an aqueous phase.

[0011] The ionic liquid is dissolved in the lubricating oil to obtain the oil phase. The oil phase is slowly added to the aqueous phase and stirred and emulsified at a stirring speed of 5000~15000 r / min for 5~15 min to obtain the emulsion.

[0012] Adjust the pH of the emulsion to 2-4 with hydrochloric acid, and then slowly add silica sol dropwise while stirring at 150-500 r / min. After the addition is complete, the microcapsule reaction solution is obtained. Continue the reaction for 12-48 h to obtain magnetic oil-containing microcapsules.

[0013] (2) Preparation of magnetic oil-containing microcapsule slurry: According to the weight percentage, the weighed magnetic oil-containing microcapsules are added to the solvent and ultrasonically dispersed to obtain magnetic oil-containing microcapsule slurry.

[0014] (3) Coating preparation: The epoxy resin and curing agent are dissolved in the magnetic oil-containing microcapsule slurry in a weight percentage to form a coating.

[0015] (4) Coating preparation: The coating is applied to the metal surface, and after the coating is surface dry, it is heated and cured to obtain a low-friction, fast-response and microwave-absorbing integrated coating.

[0016] Optionally, in the preparation steps of the magnetic oil-containing microcapsules, the raw materials and their weight parts include: 100 parts of deionized water, 0.5~2.5 parts of composite emulsifier, 0.5~5 parts of magnetic nanoparticles, 10~30 parts of lubricating oil, 0.1~1 parts of ionic liquid and 15~50 parts of silica sol.

[0017] Optionally, the composite emulsifier is a mixture of nonionic emulsifier OP-10 and cationic emulsifier cetyl ammonium chloride in a weight ratio of 2-3:1.

[0018] Optionally, the magnetic nanoparticles are FeCo alloy, Fe3O4, or Co3O4.

[0019] Optionally, the ionic liquid is an oil-soluble ionic liquid, and the lubricating oil is a non-polar polyalphaolefin.

[0020] Optionally, the preparation method of silica sol is as follows: dissolve 10-30 parts by weight of sodium silicate in 100 parts by weight of deionized water, adjust the pH value to 2-4 with hydrochloric acid, and obtain silica sol.

[0021] Optionally, in the coating preparation step, the curing conditions are: curing at 80-90℃ for 6-10 hours.

[0022] The application and preparation method of the low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules provided in this application achieve a coating with low friction coefficient, fast response capability, and good microwave absorption performance. Compared with the prior art, it has the following advantages: (1) This application uses magnetic oil-containing microcapsules as lubricating fillers. During friction, the lubricating oil is released from the microcapsules and spreads on the coating surface (friction interface) in a very short time to form a lubricating film. The magnetic nanoparticles can repair wear defects and enhance the interaction between the lubricating oil and the friction interface. The synergistic structure-property relationship between the two greatly reduces the running-in time and achieves low-friction ultrafast response. The electromagnetic loss characteristics of the magnetic nanoparticles and the cavity structure of the microcapsules synergistically improve the wave absorption performance of the material.

[0023] (2) By encapsulating and redispersing lubricating oil containing ionic liquid through a large number of microcapsule shells with small particle size, compared with adding lubricating oil directly to the coating, the shell encapsulation method of this application greatly improves the dispersion uniformity of lubricating oil. During the friction process of the equipment, the lubricating oil is released from the microcapsules and spreads on the coating surface (friction interface) in a very short time to form a uniform lubricating film. This not only improves the uniformity of the coating, but also greatly improves the lubrication performance of the coating, which helps the equipment surface to have good friction reduction and wear resistance.

[0024] (3) This application improves wave absorption performance by combining the electromagnetic loss of magnetic nanoparticles with the cavity structure of microcapsules; it combines the wear repair function of magnetic nanoparticles with the lubrication function of ionic liquid lubricating oil to achieve low friction coefficient and fast response capability; the resulting coating has both low friction, fast response and wave absorption performance. This coating has a low friction coefficient, ultra-short running-in time and good wave absorption performance, which is an effective means to solve the problem of friction and wear of moving parts of mechanical equipment under frequent start-stop and variable working conditions. At the same time, it can effectively solve the problem of interference of complex electromagnetic conditions and electromagnetic pollution on the operation of precision equipment. It can be used in the fields of automobiles, aerospace and marine, military equipment, machinery manufacturing, wind power, etc., to improve equipment energy efficiency, reduce maintenance costs and ensure stable operation of equipment in complex electromagnetic environments. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 A flowchart illustrating the preparation of magnetic oil-containing microcapsules according to an embodiment of this application; Figure 2 A surface morphology diagram of a low-friction, fast-response, and microwave-absorbing integrated coating provided in an embodiment of this application; Figure 3 Surface morphology diagram of a low-friction, fast-response, and integrated microwave-absorbing coating provided in another embodiment of this application; Figure 4 This is a schematic diagram of the friction coefficient in Embodiment 2 of this application; Figure 5 This is a schematic diagram of the friction coefficient for Comparative Example 1 of this application; Figure 6 This is a schematic diagram of the friction coefficient for Comparative Example 2 of this application; Figure 7 This is a schematic diagram showing the friction coefficient of the pure epoxy resin coating in this application; Figure 8 This is a comparison chart of the frictional properties of Example 2, Examples 4-6, Comparative Example 1, and Comparative Example 2 of this application; Figure 9 The surface morphology of the wear marks in Example 2 of this application and the pure epoxy resin coating is shown under an optical microscope. Figure 10 This is a test diagram of the absorption performance of Embodiment 2 of this application. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are also within the scope of protection of this application.

[0028] On one hand, this application provides the use of a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules, which is used to prepare materials with integrated anti-corrosion and microwave-absorbing properties. The coating is composed of the following components by weight percentage: 15-25% epoxy resin, 5-15% curing agent, 1-5% magnetic oil-containing microcapsules, and the balance being solvent.

[0029] Magnetic oil-containing microcapsules include a microcapsule shell material and an ionic liquid and lubricating oil encapsulated within the microcapsule shell material. The microcapsule shell material includes a wall capsule monomer and magnetic nanoparticles embedded within the wall capsule monomer.

[0030] The solvent used is a mixture of xylene and n-butanol in a weight ratio of 1:1-2.

[0031] Specifically, in the low-friction, fast-response, and microwave-absorbing integrated coating provided in this application, epoxy resin serves as the binder, and magnetic oil-containing microcapsules are uniformly dispersed in the epoxy resin film, forming a robust protective layer that prevents external factors such as moisture and chemicals from corroding the substrate, while also providing good lubrication for the equipment surface. The curing agent promotes the coating's curing efficiency. This application also uses magnetic oil-containing microcapsules as a lubricating filler. These microcapsules include a microcapsule shell and an ionic liquid and lubricating oil encapsulated within it, organically combining the ionic liquid-containing lubricating oil and magnetic nanoparticles. Microcapsule encapsulation solves problems such as incompatibility, lack of curing, and decreased mechanical properties associated with directly adding lubricating oil to the coating. The addition of the ionic liquid improves the lubrication performance of the lubricating oil; the magnetic nanoparticles can repair wear defects and enhance the interaction between the lubricating oil and the friction interface. The two work synergistically to significantly reduce the running-in time of the friction surface during equipment startup, achieving a low steady-state friction coefficient and ultra-fast response speed. Simultaneously, the electromagnetic loss characteristics of the magnetic nanoparticles and the cavity structure of the microcapsules work together to greatly improve the material's microwave absorption performance.

[0032] Among them, the magnetic oil-containing microcapsules have a particle size of 2-5 μm, which is beneficial for the dispersion and encapsulation of lubricating oil and ionic liquid within the shell, improving the dispersion uniformity of lubricating oil and ionic liquid, enhancing the lubrication performance of the coating, and achieving an ultrafast response speed on the coating surface. At the same time, the uniformly distributed magnetic nanoparticles can improve the wave absorption performance of the material.

[0033] This application provides a low-friction, fast-response, and integrated microwave absorption coating through the aforementioned scheme. By employing magnetic oil-containing microcapsules as lubricating fillers, lubricating oil is released from the microcapsules during friction, spreading and forming a lubricating film on the coating surface (friction interface) in a very short time. Magnetic nanoparticles can repair wear defects and enhance the interaction between the lubricating oil and the friction interface. The synergistic structure-property relationship between these two significantly reduces the break-in time, achieving a low-friction, ultra-fast response. The electromagnetic loss characteristics of the magnetic nanoparticles and the cavity structure of the microcapsules synergistically improve the microwave absorption performance of the material. The low-friction, fast-response, and integrated microwave absorption coating provided by this application can be used in automotive, aerospace, marine, military equipment, machinery manufacturing, wind power, and other fields, improving equipment energy efficiency, reducing equipment maintenance costs, and ensuring stable operation of equipment in complex electromagnetic environments.

[0034] Optionally, the wall capsule monomer can be any one of silica sol, urea-formaldehyde resin, acrylic resin, or polyurethane resin.

[0035] Specifically, silica sol, urea-formaldehyde resin, acrylic resin, and polyurethane resin are used as wall monomers. Magnetic nanoparticles are embedded within the wall monomers to form microcapsule shells, which encapsulate ionic liquids and lubricating oils, forming magnetic oil-containing microcapsules. These magnetic oil-containing microcapsules are then dispersed in a solvent and epoxy resin, and finally cured with a curing agent to form a coating. This design, using a large number of small-particle-size microcapsule shells to encapsulate and redisperse the lubricating oil containing ionic liquids, significantly improves the uniformity of lubricating oil dispersion compared to directly adding the lubricating oil to the coating. During equipment friction, the lubricating oil and ionic liquid are released from the microcapsules and spread on the coating surface (friction interface) in a very short time to form a uniform lubricating film. This not only improves the uniformity of the coating but also greatly enhances its lubrication performance, contributing to excellent friction-reducing and wear-resistant properties on the equipment surface.

[0036] More preferably, the wall capsule monomer is silica sol. Silica sol is a dispersion of nano-sized silica particles in water or a solvent, used as a material for thin-shell precision casting. In microcapsules formed using silica sol, magnetic nanoparticles are embedded between the silica wall capsule monomers. In the prior art, silica microcapsules are mainly used for coating phase change energy storage materials. In this application, silica is used as the wall capsule monomer. Compared to currently reported microcapsules in the lubrication field, which mostly use polymers as shell materials, silica microcapsules have stronger mechanical properties, and the prepared coating has a short running-in time, which can meet the friction reduction and wear resistance requirements of equipment under frequent start-stop and variable operating conditions. Furthermore, it can embed magnetic nanoparticles, exhibiting excellent wave absorption properties.

[0037] Optionally, the curing agent is an amine-based curing agent.

[0038] Specifically, amine curing agents have high reactivity, fast curing speed, and the cured products have good adhesion, flexibility, water resistance, and chemical resistance, which promotes the mechanical properties of the coating.

[0039] Furthermore, amine curing agents include one of polyetheramine, isophorone diamine (IPDA), 3,3′-dimethyl-4,4′-diamino-dicyclohexylmethane, tetraethylenepentamine, and triethylenetetramine.

[0040] On the other hand, such as Figure 1 As shown, this application provides a method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules. The method comprises the following steps: (1) Preparation of magnetic oil-containing microcapsules: The composite emulsifier was dissolved in deionized water to form a clear solution, and the magnetic nanoparticles were ultrasonically dispersed in the clear solution to obtain an aqueous phase.

[0041] The ionic liquid is dissolved in the lubricating oil to obtain the oil phase. The oil phase is slowly added to the aqueous phase and stirred and emulsified at a stirring speed of 5000~15000 r / min for 5~15 min to obtain the emulsion.

[0042] Adjust the pH of the emulsion to 2-4 with hydrochloric acid, and then slowly add silica sol dropwise while stirring at 150-500 r / min. After the addition is complete, the microcapsule reaction solution is obtained. Continue the reaction for 12-48 h to obtain magnetic oil-containing microcapsules.

[0043] (2) Preparation of magnetic oil-containing microcapsule slurry: According to the weight percentage, the weighed magnetic oil-containing microcapsules are added to the solvent and ultrasonically dispersed to obtain magnetic oil-containing microcapsule slurry.

[0044] (3) Coating preparation: The epoxy resin and curing agent are dissolved in the magnetic oil-containing microcapsule slurry in a weight percentage to form a coating.

[0045] (4) Coating preparation: The coating is applied to the metal surface and heated to cure after the coating is surface dry, thus obtaining a low-friction, fast-response and wave-absorbing integrated coating, and at the same time, a material with integrated anti-corrosion and wave-absorbing properties is obtained.

[0046] Specifically, this application employs Pickering emulsion polymerization to prepare magnetic oil-containing microcapsules. First, a composite emulsifier is dissolved in deionized water to form a clear solution. Magnetic nanoparticles are then ultrasonically dispersed in this clear solution to obtain an aqueous phase. This ensures the magnetic nanoparticles are dispersed as much as possible in the deionized water. Next, an ionic liquid is dissolved in lubricating oil to obtain an oil phase. Under stirring, the oil phase is slowly added to the aqueous phase for emulsification, resulting in a more uniform microcapsule reaction solution. Slowly adding silica sol allows the amphiphilic magnetic nanoparticles to form stable microcapsules at the liquid interface, enhancing the mechanical properties of the microcapsules. This application organically combines lubricating oil containing ionic liquid with magnetic nanoparticles. The synergistic effect of the ionic liquid, lubricating oil, and magnetic nanoparticles achieves a low steady-state friction coefficient and ultrafast response speed. The electromagnetic loss characteristics of the magnetic nanoparticles and the cavity structure of the microcapsules work together to significantly improve the material's microwave absorption performance, resulting in a coating with a low friction coefficient, rapid response, and excellent microwave absorption properties.

[0047] In this application, the coating method is one of spraying, roller coating or brushing, and the coating thickness is 1-2 mm.

[0048] Furthermore, the preparation of magnetic oil-containing microcapsules also includes: after the reaction is completed, crude magnetic oil-containing microcapsules are obtained, the crude magnetic oil-containing microcapsules are washed multiple times with deionized water and petroleum ether to remove uncoated lubricating oil, the washed microcapsules are obtained by suction filtration, and finally dried at 70-80℃ until the weight remains stable to obtain magnetic oil-containing microcapsules.

[0049] Furthermore, the coating for the low-friction, fast-response, and integrated microwave absorption coating also contains 0.3-0.5% porous biomass carbon and 0.06-0.1% N-methyl-2-hydroxyethylamine. During coating preparation, after the preparation of the magnetic oil-containing microcapsules is completed, solvent is taken by weight percentage, and 50-70% of the solvent weight is mixed with the magnetic oil-containing microcapsules to obtain a magnetic oil-containing microcapsule slurry. Simultaneously, the porous biomass carbon is ultrasonically dispersed in the remaining solvent to obtain a porous biomass carbon dispersion. Finally, the porous biomass carbon dispersion, epoxy resin, and curing agent are successively dissolved in the magnetic oil-containing microcapsule slurry, and ultrasonic dispersion is continued for 0.5-1 h to form the coating.

[0050] After dispersing the magnetic oil-containing microcapsules and porous biomass carbon separately in a solvent, they are then mixed with epoxy resin and a curing agent. This allows the magnetic oil-containing microcapsules and porous biomass carbon to be uniformly dispersed in the solvent first, preventing particle agglomeration caused by direct mixing.

[0051] The preparation of porous biomass carbon includes: ultrasonically cleaning ginkgo leaves in anhydrous ethanol for 0.5-2 hours, then drying them in an oven at 60-70℃ for 0.5-1 hours to obtain dried ginkgo leaves. The dried ginkgo leaves are then placed in a carbonization furnace and carbonized at 400-550℃ for 1-3 hours under nitrogen protection to obtain carbonized ginkgo leaves. The carbonized ginkgo leaves are then mixed with N-methyl-2-hydroxyethylamine and ground to 150-300 mesh to obtain porous biomass carbon.

[0052] Porous biomass carbon, obtained by carbonizing ginkgo leaves, is added to the coating. Therefore, the surface of the porous biomass carbon has a porous structure and a large specific surface area. This allows the magnetic oil-containing microcapsule slurry to be adsorbed into the pores of the porous biomass carbon surface when the porous biomass carbon dispersion is mixed with it. This not only makes the dispersion of the magnetic oil-containing microcapsules more uniform but also improves their stability in the coating, further preventing their aggregation and enhancing the uniformity of the coating. This helps the coating better perform its lubrication and wave absorption properties. Meanwhile, during the friction process, porous biomass carbon acts as a filler, filling the ink stain surface and providing a buffering effect. Simultaneously, under the influence of friction, the microcapsules adsorbed within the pores of the porous biomass carbon release lubricating oil, which spreads rapidly across the coating surface to form a uniform lubricating film. The combined effect of porous biomass carbon and microcapsules enhances the rapid lubrication performance of the coating. Furthermore, the electromagnetic loss characteristics of the magnetic nanoparticles and the cavity structure of the microcapsules work synergistically during friction, further enhancing the wave absorption performance of the coating. The porous biomass carbon comprises 0.3–0.5% by weight, while the magnetic oil-containing microcapsules comprise 1–5% by weight. The lower amount of porous biomass carbon compared to the magnetic oil-containing microcapsules has no impact on the release rate of lubricating oil and ionic liquid from the microcapsules during friction, and further improves the dispersion stability of the magnetic oil-containing microcapsules.

[0053] After carbonizing ginkgo leaves, the carbonized ginkgo leaves are mixed with N-methyl-2-hydroxyethylamine and ground to 150-300 mesh to obtain porous biomass carbon. The hydroxyl groups in N-methyl-2-hydroxyethylamine can activate the carbonized ginkgo leaves under the pressure and heat generated during the grinding process, further increasing the porosity of the surface and obtaining porous biomass carbon. This, in turn, enhances the adsorption of magnetic oil-containing microcapsules by the porous biomass carbon, thereby strengthening the coating's low-friction, rapid response and integrated wave absorption performance during equipment friction. This performance facilitates the application of the coating in surface lubrication conditions during rapid start-up and shutdown of equipment, achieving a low steady-state friction coefficient and ultra-fast response speed. Simultaneously, the coating of this application exhibits excellent wave absorption performance, contributing to the long-term stable operation of the equipment.

[0054] The ginkgo leaves used in this application as raw materials for porous biochar are inexpensive and the method is simple, which is conducive to large-scale production.

[0055] Optionally, the raw materials used in the preparation steps of the magnetic oil-containing microcapsules and their weight parts include: 100 parts of deionized water, 0.5-2.5 parts of composite emulsifier, 0.5-5 parts of magnetic nanoparticles, 10-30 parts of lubricating oil, 0.1-1 parts of ionic liquid and 15-50 parts of silica sol by weight.

[0056] Specifically, in the preparation steps of magnetic oil-containing microcapsules, the weight ratio of each raw material is controlled to achieve the formation of the microcapsule shell material, and then the lubricating oil of the dissolved ionic liquid is encapsulated in the microcapsule shell material, thereby enabling control over the synthesis of magnetic oil-containing microcapsules.

[0057] Optionally, the composite emulsifier is a mixture of nonionic emulsifier OP-10 and cationic emulsifier cetyl ammonium chloride in a weight ratio of 2-3:1.

[0058] Specifically, composite emulsifiers can effectively regulate the HLB value (HLB value refers to the hydrophilic-lipophilic balance value) of emulsifiers, which is beneficial to improving the stability of emulsions. The orderly distribution of amphiphilic magnetic nanoparticles at the water-oil interface can further improve the stability of emulsions, thereby contributing to the formation of magnetic oil-containing microcapsules.

[0059] Optionally, the magnetic nanoparticles are FeCo alloy, Fe3O4, or Co3O4.

[0060] Specifically, combining the electromagnetic loss of magnetic nanoparticles with the cavity structure of microcapsules improves wave absorption performance; at the same time, combining the wear repair function of magnetic nanoparticles with the lubrication function of ionic liquids and lubricating oils achieves low friction coefficient and fast response capability; thus, it helps the coating to have both low friction, fast response and wave absorption performance.

[0061] Optionally, the ionic liquid is an oil-soluble ionic liquid, and the lubricating oil is a non-polar polyalphaolefin.

[0062] Specifically, the ionic liquid is an ammonium phosphate ionic liquid, and the lubricating oil is one or more of PAO2, PAO46, and PAO6.

[0063] Optionally, the preparation method of silica sol is as follows: dissolve 10-30 parts of sodium silicate in 100 parts of deionized water, adjust the pH value to 2-4 with hydrochloric acid, and obtain silica sol.

[0064] Optionally, in the coating preparation step, the curing conditions are: curing at 80-90℃ for 6-10 hours.

[0065] Specifically, controlling the curing temperature to 80-90℃ is not only beneficial for the curing of the coating, but also for the smoothness of the coating.

[0066] The present invention will be further described in detail below with reference to embodiments. However, it should be understood that the embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0067] Example 1 The application and preparation method of low-friction, fast-response, and microwave-absorbing integrated coatings based on magnetic oil-containing microcapsules include the following steps: (1) Preparation of magnetic oil-containing microcapsules: The composite emulsifier was dissolved in deionized water to form a clear solution. The magnetic nanoparticles were ultrasonically dispersed in the clear solution to obtain an aqueous phase. The magnetic nanoparticles were FeCo alloy.

[0068] Ammonium phosphate ionic liquid was dissolved in PAO2 lubricating oil to obtain the oil phase. The oil phase was slowly added to the aqueous phase and emulsified by stirring at 5000 r / min for 5 min to obtain the emulsion.

[0069] Dissolve 10 parts sodium silicate in 100 parts deionized water, and adjust the pH to 2 with hydrochloric acid to obtain silica sol.

[0070] The pH of the emulsion was adjusted to 2 with hydrochloric acid, and then silica sol was slowly added dropwise while stirring at 15 r / min. After the addition was complete, the microcapsule reaction solution was obtained, and the reaction was continued for 12 h. After the reaction was completed, crude magnetic oil-containing microcapsules were obtained. The crude magnetic oil-containing microcapsules were washed multiple times with deionized water and petroleum ether to remove the uncoated lubricating oil. The washed microcapsules were obtained by suction filtration and finally dried at 70 °C until the weight remained stable to obtain the magnetic oil-containing microcapsules.

[0071] The raw materials and their weight ratios in the preparation of magnetic oil-containing microcapsules are as follows: 100 parts by weight of deionized water, 0.5 parts by weight of composite emulsifier, 0.5 parts by weight of magnetic nanoparticles, 10 parts by weight of lubricating oil, 0.1 parts by weight of ionic liquid, and 15 parts by weight of silica sol.

[0072] The composite emulsifier is a mixture of nonionic emulsifier OP-10 and cationic emulsifier cetyl ammonium chloride in a weight ratio of 2:1.

[0073] (2) Preparation of magnetic oil-containing microcapsule slurry: According to the weight percentage, the weighed magnetic oil-containing microcapsules are added to the solvent and ultrasonically dispersed to obtain magnetic oil-containing microcapsule slurry.

[0074] The coating is composed of the following components by weight percentage: 15% epoxy resin, 5% curing agent, 1% magnetic oil-containing microcapsules, and the balance being solvent.

[0075] (3) Coating preparation: The epoxy resin and curing agent are dissolved in the magnetic oil-containing microcapsule slurry in sequence according to the weight percentage to form the coating. The curing agent is polyetheramine, and the solvent is a mixture of xylene and n-butanol in a weight ratio of 1:1.

[0076] (4) Coating preparation: The coating is sprayed onto the metal surface, and after the coating is surface dry, it is heated and cured to obtain a low-friction, fast-response, and microwave-absorbing integrated coating. The curing conditions are: 80-90℃ for 6 hours.

[0077] Example 2

[0078] The application and preparation method of low-friction, fast-response, and microwave-absorbing integrated coatings based on magnetic oil-containing microcapsules include the following steps: The difference from Example 1 is as follows: (1) Preparation of magnetic oil-containing microcapsules: The magnetic nanoparticles in the aqueous phase are Fe3O4.

[0079] Ammonium phosphate ionic liquid was dissolved in PAO6 lubricating oil to obtain the oil phase. The oil phase was slowly added to the aqueous phase and emulsified by stirring at 12000 r / min for 10 min to obtain the emulsion.

[0080] Dissolve 20 parts of sodium silicate in 100 parts of deionized water, and adjust the pH to 2.95 with hydrochloric acid to obtain silica sol.

[0081] The pH of the emulsion was adjusted to 2.95 with hydrochloric acid, and silica sol was slowly added dropwise while stirring at 250 r / min. After the addition was complete, the microcapsule reaction solution was obtained, and the reaction was continued for 24 h. After the reaction was completed, crude magnetic oil-containing microcapsules were obtained. The crude magnetic oil-containing microcapsules were washed multiple times with deionized water and petroleum ether to remove the uncoated lubricating oil. The washed microcapsules were obtained by suction filtration and finally dried at 80 °C until the weight remained stable to obtain the magnetic oil-containing microcapsules.

[0082] The raw materials and their weight ratios in the preparation of magnetic oil-containing microcapsules are as follows: 100 parts by weight of deionized water, 1.5 parts by weight of composite emulsifier, 3 parts by weight of magnetic nanoparticles, 20 parts by weight of lubricating oil, 0.6 parts by weight of ionic liquid, and 30 parts by weight of silica sol.

[0083] The composite emulsifier is a mixture of nonionic emulsifier OP-10 and cationic emulsifier cetyl ammonium chloride in a weight ratio of 3:1.

[0084] (3) Coating preparation: The epoxy resin and curing agent are dissolved in the magnetic oil-containing microcapsule slurry in sequence according to the weight percentage to form the coating. The curing agent is polyetheramine, and the solvent is a mixture of xylene and n-butanol with a weight ratio of 1:2.

[0085] The coating is composed of the following components by weight percentage: 20% epoxy resin, 10% curing agent, 3% magnetic oil-containing microcapsules, and the balance being solvent.

[0086] (4) Coating preparation: The coating is sprayed onto the metal surface and heated to cure after the coating is surface dry, thus obtaining a low-friction, fast-response, and microwave-absorbing integrated coating. The curing conditions are: 90℃ for 8 hours.

[0087] Example 3

[0088] The application and preparation method of low-friction, fast-response, and microwave-absorbing integrated coatings based on magnetic oil-containing microcapsules include the following steps: The difference from Example 1 is as follows: (1) Preparation of magnetic oil-containing microcapsules: The magnetic nanoparticles in the aqueous phase are Co3O4.

[0089] Ammonium phosphate ionic liquid was dissolved in PAO46 lubricating oil to obtain the oil phase. The oil phase was slowly added to the aqueous phase, and the mixture was stirred and emulsified at a stirring speed of 15000 r / min for 15 min to obtain the emulsion.

[0090] Dissolve 10-30 parts of sodium silicate in 100 parts of deionized water, and adjust the pH to 4 with hydrochloric acid to obtain silica sol.

[0091] The pH of the emulsion was adjusted to 4 with hydrochloric acid, and then silica sol was slowly added dropwise while stirring at 500 r / min. After the addition was complete, the microcapsule reaction solution was obtained, and the reaction was continued for 48 h. After the reaction was completed, crude magnetic oil-containing microcapsules were obtained. The crude magnetic oil-containing microcapsules were washed multiple times with deionized water and petroleum ether to remove the uncoated lubricating oil. The washed microcapsules were obtained by suction filtration and finally dried at 80 °C until the weight remained stable to obtain the magnetic oil-containing microcapsules.

[0092] The raw materials and their weight ratios in the preparation of magnetic oil-containing microcapsules are as follows: 100 parts by weight of deionized water, 2.5 parts by weight of composite emulsifier, 5 parts by weight of magnetic nanoparticles, 30 parts by weight of lubricating oil, 1 part by weight of ionic liquid, and 50 parts by weight of silica sol.

[0093] The composite emulsifier is a mixture of nonionic emulsifier OP-10 and cationic emulsifier cetyl ammonium chloride in a weight ratio of 3:1.

[0094] (3) Coating preparation: The epoxy resin and curing agent are dissolved in the magnetic oil-containing microcapsule slurry in sequence according to the weight percentage to form the coating. The curing agent is polyetheramine, and the solvent is a mixture of xylene and n-butanol with a weight ratio of 1:2.

[0095] The coating is composed of the following components by weight percentage: 25% epoxy resin, 15% curing agent, 5% magnetic oil-containing microcapsules, and the balance being solvent.

[0096] (4) Coating preparation: The coating is sprayed onto the metal surface and heated to cure after the coating is surface dry, thus obtaining a low-friction, fast-response, and microwave-absorbing integrated coating. The curing conditions are: curing at 90℃ for 10 hours.

[0097] Example 4

[0098] The application and preparation method of low-friction, fast-response, and microwave-absorbing integrated coatings based on magnetic oil-containing microcapsules include the following steps: The difference from Example 2 is that: (1) Preparation of magnetic oil-containing microcapsules.

[0099] (2) Preparation of porous biomass carbon: Ginkgo leaves were ultrasonically cleaned in anhydrous ethanol for 0.5 h, then placed in an oven and dried at 60 °C for 0.5 h to obtain dried ginkgo leaves. The dried ginkgo leaves were then placed in a carbonization furnace and carbonized at 400 °C for 1 h under nitrogen protection to obtain carbonized ginkgo leaves. The carbonized ginkgo leaves were mixed with N-methyl-2-hydroxyethylamine and ground to 150 mesh to obtain porous biomass carbon.

[0100] (3) Preparation of magnetic oil-containing microcapsule slurry: Take solvent by weight percentage, and mix 50% of the solvent weight with the weighed magnetic oil-containing microcapsules, and disperse by ultrasonication to obtain magnetic oil-containing microcapsule slurry.

[0101] (4) Preparation of porous biomass carbon dispersion: The porous biomass carbon is ultrasonically dispersed in the remaining solvent to obtain a porous biomass carbon dispersion.

[0102] (5) Coating preparation: The porous biomass carbon dispersion, epoxy resin and curing agent are dissolved in the magnetic oil-containing microcapsule slurry in sequence according to the weight percentage, and ultrasonic dispersion is continued for 0.5h to form a coating.

[0103] The coating is composed of the following components by weight percentage: 20% epoxy resin, 10% curing agent, 3% magnetic oil-containing microcapsules, 0.3% porous biomass carbon, 0.06% N-methyl-2-hydroxyethylamine, and the balance being solvent.

[0104] (6) Coating preparation: The coating is sprayed onto the metal surface, and after the coating is surface dry, it is heated and cured to obtain a low-friction, fast-response, and microwave-absorbing integrated coating. The curing conditions are: 90℃ for 8 hours.

[0105] Example 5

[0106] The application and preparation method of low-friction, fast-response, and microwave-absorbing integrated coatings based on magnetic oil-containing microcapsules include the following steps: The difference from Example 2 is that: (2) Preparation of porous biomass carbon: Ginkgo leaves were ultrasonically cleaned in anhydrous ethanol for 1.5 h, then placed in an oven and dried at 65 °C for 1 h to obtain dried ginkgo leaves. The dried ginkgo leaves were then placed in a carbonization furnace and carbonized at 500 °C for 2 h under nitrogen protection to obtain carbonized ginkgo leaves. The carbonized ginkgo leaves were mixed with N-methyl-2-hydroxyethylamine and ground to 200 mesh to obtain porous biomass carbon.

[0107] (3) Preparation of magnetic oil-containing microcapsule slurry: Take solvent by weight percentage, and mix 60% of the solvent weight with the weighed magnetic oil-containing microcapsules, and disperse by ultrasonication to obtain magnetic oil-containing microcapsule slurry.

[0108] (5) Coating preparation: According to the weight percentage, the porous biomass carbon dispersion, epoxy resin and curing agent are dissolved in the magnetic oil-containing microcapsule slurry, and ultrasonic dispersion is continued for 1 hour to form a coating.

[0109] The coating is composed of the following components by weight percentage: 20% epoxy resin, 10% curing agent, 3% magnetic oil-containing microcapsules, 0.4% porous biomass carbon, 0.08% N-methyl-2-hydroxyethylamine, and the balance being solvent.

[0110] Example 6

[0111] The application and preparation method of low-friction, fast-response, and microwave-absorbing integrated coatings based on magnetic oil-containing microcapsules include the following steps: The difference from Example 2 is that: (2) Preparation of porous biomass carbon: Ginkgo leaves were ultrasonically cleaned in anhydrous ethanol for 2 hours, then placed in an oven and dried at 70°C for 1 hour to obtain dried ginkgo leaves. The dried ginkgo leaves were then placed in a carbonization furnace and carbonized at 550°C for 3 hours under nitrogen protection to obtain carbonized ginkgo leaves. The carbonized ginkgo leaves were mixed with N-methyl-2-hydroxyethylamine and ground to 300 mesh to obtain porous biomass carbon.

[0112] (3) Preparation of magnetic oil-containing microcapsule slurry: Take solvent by weight percentage, and mix 70% of the solvent weight with the weighed magnetic oil-containing microcapsules, and disperse by ultrasonication to obtain magnetic oil-containing microcapsule slurry.

[0113] (5) Coating preparation: According to the weight percentage, the porous biomass carbon dispersion, epoxy resin and curing agent are dissolved in the magnetic oil-containing microcapsule slurry, and ultrasonic dispersion is continued for 1 hour to form a coating.

[0114] The coating is composed of the following components by weight percentage: 20% epoxy resin, 10% curing agent, 3% magnetic oil-containing microcapsules, 0.5% porous biomass carbon, 0.1% N-methyl-2-hydroxyethylamine, and the balance being solvent.

[0115] Comparative Example 1 The difference from Example 1 is as follows: (1) Preparation of magnetic oil-containing microcapsules: No magnetic nanoparticles were added.

[0116] Comparative Example 2 The difference from Example 1 is as follows: (1) Preparation of magnetic oil-containing microcapsules: No ionic liquid was added.

[0117] Experimental Example 1 Coating morphology analysis The low-friction, fast-response, and microwave-absorbing integrated coating prepared in Example 2 was photographed under an optical microscope, as shown below. Figure 2 and Figure 3 The image shown is an optical micrograph of the coating of this application at different magnifications.

[0118] Depend on Figure 2 and Figure 3 It can be seen that the magnetic oil-containing microcapsules in the low-friction, fast-response, and microwave-absorbing integrated coating provided in this application exhibit relatively uniform dispersion. This indicates that by encapsulating and redispersing the lubricating oil containing ionic liquid through the microcapsule shell, the shell encapsulation method of this application significantly improves the uniformity of lubricating oil dispersion. During equipment friction, the lubricating oil is released from the microcapsules and spreads to form a uniform lubricating film on the coating surface (friction interface) in a very short time. This not only improves the uniformity of the coating but also greatly enhances its lubrication performance, contributing to excellent friction-reducing and wear-resistant properties on the equipment surface.

[0119] Experimental Example 2 Tribological property analysis of coating The coatings obtained in Example 2, Comparative Example 1, and Comparative Example 2 were subjected to tribological performance tests, and their lubrication performance was compared with that of a pure epoxy resin coating. The results are as follows: Figures 4-7 As shown.

[0120] Meanwhile, the running-in time and steady-state friction coefficient of Example 2 were compared with those of Examples 4-6, Comparative Example 1, and Comparative Example 2, and the results were as follows: Figure 8 The results are shown.

[0121] Test conditions: ball-disc contact, reciprocating wear, load: 5N, frequency: 2Hz, amplitude: 8mm, and the counterpart is a 316L steel ball with a diameter of 6mm.

[0122] Depend on Figures 4-7 It can be seen that the coating provided in this application, compared with the coatings provided by pure epoxy resin, Comparative Example 1, and Comparative Example 2, not only has a stable coefficient of friction (COF) during tribological performance testing, but also has a significantly lower steady-state coefficient of friction. Furthermore, the running-in time is almost 0 seconds. In Comparative Example 1, without the addition of magnetic nanoparticles, although the steady-state coefficient of friction is lower than that of the pure epoxy resin coating, the running-in time is approximately 250 seconds compared to Example 2, and approximately 160 seconds in Comparative Example 2. This indicates that the coating provided in this application has a lower steady-state coefficient of friction and a faster response speed. When applied to the surface of equipment, it maintains excellent friction-reducing and wear-resistant properties even under conditions of equipment start-up, shutdown, and changes in operating conditions. This is beneficial for equipment protection, reduces the frequency of equipment maintenance and replacement, and promotes long-term stable operation of the equipment.

[0123] observe Figure 8 Comparing Examples 2 with Examples 4-6, it can be seen that after adding porous biomass carbon and N-methyl-2-hydroxyethylamine to the coating, the running-in time of the coating is still 0 seconds, and the steady-state friction coefficient of the coating is even smaller. This indicates that the addition of porous biomass carbon and N-methyl-2-hydroxyethylamine improves the lubrication performance of the coating. At the same time, during the equipment start-up and shutdown phase, the microcapsules adsorbed in the pores of the porous biomass carbon release lubricating oil from the microcapsules under the action of friction, spreading and forming a uniform lubricating film on the coating surface in a very short time. The combined effect of porous biomass carbon and microcapsules improves the rapid lubrication performance of the coating, and the coating still maintains a fast response speed. This not only gives the equipment surface good friction reduction and wear resistance, but also maintains the stability of the equipment during the start-up and shutdown phase, avoiding the jamming phenomenon caused by high friction during the start-up and shutdown phase, realizing the smooth start-up of the equipment, and thus improving the operational stability of the equipment.

[0124] Experimental Example 3 Coating wear morphology analysis The scratched surfaces of Example 2 and the pure epoxy resin coating were photographed under an optical microscope (SEM) to obtain the following results: Figure 9 The results are shown.

[0125] Figure 9 In the figures (a) and (b), the surface morphology of the wear marks on the pure resin coating is shown, and (c) and (d) are the surface morphology of the wear marks on the coating provided in Example 2.

[0126] Depend on Figure 9It can be seen that the wear surface of the pure resin coating exhibits obvious adhesive wear and plastic fracture, with a wear mark width of 616 micrometers. In contrast, the wear mark of the coating in Example 2 is smooth, with a width of 386 micrometers. This demonstrates that by using magnetic oil-containing microcapsules as lubricating fillers, the lubricating oil is released from the microcapsules during friction and spreads to form a lubricating film on the coating surface (friction interface) in a very short time. Magnetic nanoparticles can repair wear mark defects and enhance the interaction between the lubricating oil and the friction interface. The synergistic structure-property relationship between these two factors significantly reduces the break-in time, achieving a low-friction, ultrafast response.

[0127] Experiment Example 4 Analysis of Coating Absorption Performance The microwave absorption performance of the coatings obtained in Example 2, Comparative Example 1, and Comparative Example 2 was tested using the coaxial method, and compared with the microwave absorption performance of the pure epoxy resin coating. The inner diameter of the coaxial ring was 3 mm and the outer diameter was 7 mm. The test frequency range was 2-18 GHz. The difference in the frequency range where the reflection loss was less than -10 dB was taken as the effective absorption bandwidth. The coating thickness was 2 mm. At least three parallel experiments were performed for each test example. The results are as follows: Figure 10 As shown.

[0128] Meanwhile, using the same testing method, the absorption performance of Example 2 was compared with that of Examples 4-6. Each test example had at least 3 parallel experiments, and the results are shown in Table 1.

[0129] Table 1

[0130] Experimental Results: Comparative Example 1, Comparative Example 2, and the pure epoxy resin coating showed no microwave absorption, while the coating provided in Example 2 exhibited an effective absorption bandwidth (reflection loss below -10dB) of 7.9GHz at a thickness of 1.6mm, demonstrating superior microwave absorption performance. This indicates that the electromagnetic loss characteristics of the magnetic nanoparticles and the cavity structure of the microcapsules synergistically enhance the microwave absorption performance of the material. Furthermore, as shown in Table 1, compared to Example 1, the addition of porous biomass carbon and N-methyl-2-hydroxyethylamine to the coatings of Examples 4-6 significantly increased the effective absorption bandwidth of the coating, further enhancing its microwave absorption performance. This contributes to the stable operation of the equipment in complex electromagnetic environments. This demonstrates the combined effect of porous biomass carbon and microcapsules; the adsorption effect of the porous biomass carbon allows for a more uniform distribution of the microcapsules, contributing to the synergistic effect of the electromagnetic loss characteristics of the magnetic nanoparticles and the cavity structure of the microcapsules, thereby enhancing the microwave absorption performance of the coating. Meanwhile, the porous structure of porous biomass carbon has good thermal conductivity, which can effectively dissipate heat during friction to avoid overheating and damage to the coating. It also greatly promotes the low-friction rapid response and wave absorption performance of the protective coating.

[0131] Experimental Example 5 Mechanical property analysis of coating The main mechanical properties of the coatings provided in Examples 2, 5, 1, and 2 were tested. Each experiment was performed in at least three parallel tests, and the average value was taken. The results are shown in Table 2.

[0132] The testing standards in the experimental examples are as follows: (1) Appearance: The coating of each experimental example is uniform and without defects (visual inspection). (2) Coating adhesion: Cross-cut test for paints and varnishes, GB / T 9286-2021; (3) Coating flexibility: GB / T 1731-2020 Test method for flexibility of paint film and putty film; (4) Impact resistance of coating: GB / T 1732-2020 Test method for impact resistance of coating film.

[0133] Table 2

[0134] As shown in Table 2, the coating provided by this application has good mechanical properties, which ensures the coating's low-friction, fast response and integrated wave absorption performance, allowing the coating to adhere better to the equipment surface, thus facilitating the long-term stable operation of the equipment.

[0135] This application demonstrates that the coating provided has good mechanical properties, which in turn enhances the coating's lubrication and wave absorption properties, making the coating suitable for equipment surfaces under different working conditions and suitable for industry promotion.

[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. An application of a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules, characterized in that, The coating is used to prepare a material that integrates corrosion resistance and wave absorption properties; The coating used to prepare the coating consists of the following components by weight percentage: 15-25% epoxy resin, 5-15% curing agent, 1-5% magnetic oil-containing microcapsules, and the balance being solvent; The coating also includes porous biomass carbon, and the preparation method of the porous biomass carbon includes: ultrasonically cleaning ginkgo leaves in anhydrous ethanol for 0.5-2 hours, placing them in an oven and drying them at 60-70℃ for 0.5-1 hours to obtain dried ginkgo leaves, then placing the dried ginkgo leaves in a carbonization furnace and carbonizing them at a carbonization temperature of 400-550℃ for 1-3 hours under nitrogen protection to obtain carbonized ginkgo leaves, mixing the carbonized ginkgo leaves with N-methyl-2-hydroxyethylamine and grinding them to 150-300 mesh to obtain porous biomass carbon; The magnetic oil-containing microcapsule comprises a microcapsule shell and an ionic liquid and a lubricating oil encapsulated within the microcapsule shell. The microcapsule shell comprises a wall capsule monomer and magnetic nanoparticles embedded within the wall capsule monomer. The solvent is a mixture of xylene and n-butanol in a weight ratio of 1:1-2. The preparation method of the magnetic oil-containing microcapsules includes: dissolving a composite emulsifier in deionized water to form a clear solution; ultrasonically dispersing magnetic nanoparticles in the clear solution to obtain an aqueous phase; dissolving an ionic liquid in lubricating oil to obtain an oil phase; slowly adding the oil phase to the aqueous phase and stirring and emulsifying at a stirring speed of 5000~15000 r / min for 5~15 min to obtain an emulsion; adjusting the pH of the emulsion to 2~4 with hydrochloric acid; and then slowly adding silica sol dropwise at a stirring speed of 150~500 r / min. After the addition is complete, a microcapsule reaction solution is obtained, and the reaction is continued for 12~48 h to obtain the magnetic oil-containing microcapsules.

2. The application of the low-friction, fast-response, and integrated microwave-absorbing coating based on magnetic oil-containing microcapsules according to claim 1, characterized in that, The cell wall monomer is silica sol.

3. The application of the low-friction, fast-response, and integrated microwave-absorbing coating based on magnetic oil-containing microcapsules according to claim 1, characterized in that, The curing agent is an amine-based curing agent.

4. A method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules, characterized in that, The method for preparing the low-friction, fast-response, and integrated microwave-absorbing coating according to any one of claims 1-3 comprises the following steps: (1) Preparation of magnetic oil-containing microcapsule slurry: Take the solvent by weight percentage and mix 50-70% of the solvent weight with the magnetic oil-containing microcapsules to obtain magnetic oil-containing microcapsule slurry; at the same time, ultrasonically disperse porous biomass carbon in the remaining solvent to obtain porous biomass carbon dispersion. (2) Coating preparation: The porous biomass carbon dispersion, epoxy resin and curing agent are dissolved in magnetic oil-containing microcapsule slurry in sequence, and ultrasonic dispersion is continued for 0.5-1h to form a coating; (3) Coating preparation: The coating is applied to the metal surface, and after the coating is surface dry, it is heated and cured to obtain the low friction fast response and wave absorption integrated coating.

5. The method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules according to claim 4, characterized in that, The preparation steps of the magnetic oil-containing microcapsules include the following raw materials and their weight parts: 100 parts of deionized water, 0.5-2.5 parts of composite emulsifier, 0.5-5 parts of magnetic nanoparticles, 10-30 parts of lubricating oil, 0.1-1 parts of ionic liquid, and 15-50 parts of silica sol.

6. The method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules according to claim 5, characterized in that, The composite emulsifier is a mixture of nonionic emulsifier OP-10 and cationic emulsifier cetyl ammonium chloride in a weight ratio of 2-3:

1.

7. The method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules according to claim 5, characterized in that, The magnetic nanoparticles are FeCo alloy, Fe3O4, or Co3O4.

8. The method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules according to claim 7, characterized in that, The ionic liquid is an oil-soluble ionic liquid, and the lubricating oil is a non-polar polyalphaolefin.

9. The method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules according to claim 8, characterized in that, The silica sol is prepared by dissolving 10-30 parts by weight of sodium silicate in 100 parts by weight of deionized water, adjusting the pH value to 2-4 with hydrochloric acid to obtain the silica sol.

10. The method for preparing a low-friction, fast-response, and microwave-absorbing integrated coating based on magnetic oil-containing microcapsules according to claim 9, characterized in that, In the coating preparation step, the curing conditions are: curing at 80-90℃ for 6-10 hours.

Citation Information

Patent Citations

  • Magnetic microencapsulated phase change energy storage material and preparation method thereof

    CN103992774A

  • Urea formaldehyde resin microcapsule lubrication oil, lubrication oil coating material and preparation method of lubrication oil

    CN104087391A

  • Preparation method of organic-inorganic double-layer composite wall material magnetic phase change microcapsule

    CN112473581A

  • Magnetic oil-containing microcapsule, self-lubricating epoxy composite material, preparation method and application

    CN115532186A